The effect of social skill education program on adolescents in Baghdad, Iraq: a preliminary report - Kamal, Aysin; Al-Kaseer, Eman A.; Aljubori, Suhair; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: In Iraq, adolescents confront challenges, external and internal factors and their life circumstances are exacerbated by threats to their physical and mental health. Objective: To throw a light on training for life skills which in turn leads to promotion of adolescents physical and mental health. Methods: A total of 120 adolescents participated in the study (50 of them were trained for life skills and the others act as control group) for the period April 2010 to Sept. 2011. Their age was 19 ± 2.4 years with male to female ratio of 1.4:1. The program consisted of several subjects concern with physical and mental health. Positive outcomes were determined. Scores of training variables presented in mean ± SD. Student’s t test was used to examine the difference in variables between trained and untrained adolescents. Results: Scores of positive outcomes (good personal hygiene, getting enough sleep, healthy weight, got exercise, social competence (adolescent shows respect, tries to resolve conflicts and concern about self-esteem), condemnation of abuse, harassment, bullying and rape, aware about sexual transmitted diseases (STDs) including acquired immunodeficiency syndrome (AIDS), intimate relationship, awareness to teen pregnancy or abortion and family planning, concern with family life (arranged marriages) and study skills (motivation, goal setting, time management, positive study attitude and empowering concentration) were significantly higher in trained than in untrained adolescents (p= 0.023, 0.025, 0.001, 0.04, 0.025, 0.001 and 0.001, respectively). Conclusion: Life skills could be applied for promotion in mental health as well as physical health.